2018
DOI: 10.1093/ofid/ofy034
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of Liposomal Amikacin for Inhalation on Mycobacterium abcessus in Cystic Fibrosis Patients

Abstract: Mycobacterium abscessus is difficult to eradicate. At the Montpellier CF Center, we prescribed liposomal amikacin for inhalation to 5 patients with M abscessus infection. The 3 patients who completed the treatment did not have any respiratory exacerbation, showed negative cultures for M abscessus in their sputum, and stabilized their spirometric functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…The liposomes are taken up by lung macrophages, allowing for intracellular delivery of high levels of amikacin into nontuberculous mycobacterial cells (Rose et al 2014;Olivier et al 2017). In 2018, Caimmi et al (2018) reported the effect of LAI (590 mg daily) on five patients with Mycobacterium abscessus in cystic fibrosis. None of the five patients showed any side effects related to the treatment, while three patients showed improvement of their pulmonary function test values and their clinical symptoms.…”
Section: Amikacinmentioning
confidence: 99%
“…The liposomes are taken up by lung macrophages, allowing for intracellular delivery of high levels of amikacin into nontuberculous mycobacterial cells (Rose et al 2014;Olivier et al 2017). In 2018, Caimmi et al (2018) reported the effect of LAI (590 mg daily) on five patients with Mycobacterium abscessus in cystic fibrosis. None of the five patients showed any side effects related to the treatment, while three patients showed improvement of their pulmonary function test values and their clinical symptoms.…”
Section: Amikacinmentioning
confidence: 99%
“…In a small case series, Caimmi et al described five CF patients treated with ALIS for MABS (three of whom completed therapy) and none were found to have therapy-limiting side effects. 93 CF patients may be more prone to the vestibular toxicity of inhaled amikacin due to chronic exposure to parenteral aminoglycosides to treat Pseudomonas infections. 94 In the CONVERT study, which enrolled patients with amikacin-susceptible MAC as well as sputum positivity despite at least 6 months of guideline-based therapy (GBT), 29% of patients in the ALIS-GBT arm compared with 8.9% in the GBT-only arm achieved culture conversion.…”
Section: Drugs Of Emerging Efficacy Inhaled Amikacinmentioning
confidence: 99%
“…Advances have been made in the area of aerosol delivery carriers and devices. The success of inhalational therapies with liposomal amikacin (Olivier et al, 2014 ; Caimmi et al, 2018 ) and Arikayce™ (Olivier et al, 2017 ) has paved the way for new therapies in this category. The development of a multicenter clinical trial network will allow more rapid enrollment in new drug treatment trials (Kevin Winthrop, personal communication).…”
Section: Introductionmentioning
confidence: 99%